2011
DOI: 10.1002/ijc.25817
|View full text |Cite
|
Sign up to set email alerts
|

Tetrandrine induces apoptosis by activating reactive oxygen species and repressing Akt activity in human hepatocellular carcinoma

Abstract: Tetrandrine, a bisbenzylisoquinoline alkaloid component of broadly used traditional Chinese medicine, has antitumor effects against some cancers. In our study, we investigated the effects of tetrandrine on the human hepatocellular carcinoma (HCC) in vitro and in vivo. The results showed that tetrandrine effectively induced apoptosis of liver cancer cell in a dose-and time-dependent manner accompanied by alteration of cell morphology, chromatin fragmentation and caspase activation. Tetrandrine treatment also in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
89
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 130 publications
(99 citation statements)
references
References 47 publications
(50 reference statements)
7
89
3
Order By: Relevance
“…Tetrandrine is a natural bisbenzylisoquinoline and has been shown to be active against a variety of tumors, such as colon cancer (Meng et al, 2004), glioma (Chen and Tseng, 2010), ovarian cancer , and hepatocellular carcinoma (Liu et al, 2011). Notably, tetrandrine inhibits Wnt/β-catenin signaling and suppresses tumor growth of human colorectal cancer (He et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Tetrandrine is a natural bisbenzylisoquinoline and has been shown to be active against a variety of tumors, such as colon cancer (Meng et al, 2004), glioma (Chen and Tseng, 2010), ovarian cancer , and hepatocellular carcinoma (Liu et al, 2011). Notably, tetrandrine inhibits Wnt/β-catenin signaling and suppresses tumor growth of human colorectal cancer (He et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that tetrandrine is cytotoxic to RT-2 glioma cells and it has antitumor effects on subcutaneous and intracerebral gliomas, and inhibits angiogenesis in subcutaneous gliomas (31)(32)(33)(34). Tetradine induced apoptosis by activating reactive oxygen species and repressing Akt activity in human hepatocellular carcinoma HCC cells (35,36). Recently, it was reported that tetrandrine induced apoptosis and triggers caspase cascade in human bladder cancer cells (37).…”
Section: Introductionmentioning
confidence: 99%
“…Tetrandrine (Tet, Figure 1) is a compound extracted from the root of Stephania tetrandra and is often used for the treatment of rheumatism, inflammation, occlusive cardiovascular disorders and tumors [1][2][3][4][5][6][7][8] . Some early studies demonstrated that tetrandrine causes hepatotoxicity [9,10] .…”
Section: Introductionmentioning
confidence: 99%